Making Migrants’ Input Invisible: Intersections of Privilege and Otherness From a Multilevel Perspective - Palenga‐Möllenbeck, Ewa (2022)
For some years, the German public has been debating the case of migrant workers receiving German benefits for children living abroad, which has been scandalised as a case of “benefit tourism.” This points to a failure to recognise a striking imbalance between the output of the German welfare state to migrants and the input it receives from migrant domestic workers. In this article I discuss how this input is being rendered invisible or at least underappreciated by sexist, racist, and classist practices of othering. To illustrate the point, I will use examples from two empirical research projects that looked into how families in Germany outsource various forms of reproductive work to both female and male migrants from Eastern Europe. Drawing on the concept of othering developed in feminist and postcolonial literature and their ideas of how privileges and disadvantages are interconnected, I will put this example into the context of literature on racism, gender, and care work migration. I show how migrant workers fail to live up to the normative standards of work, family life, and gender relations and norms set by a sedentary society. A complex interaction of supposedly “natural” and “objective” differences between “us” and “them” are at work to justify everyday discrimination against migrants and their institutional exclusion. These processes are also reflected in current political and public debates on the commodification and transnationalisation of care.